Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Bridging From Monitoring to Solutions-Based Thinking: Lessons From CalCOFI for Understanding and Adapting to Marine Climate Change Impacts - Natalya D. Gallo; Elizabeth Drenkard; Andrew R. Thompson; Edward D. Weber; Deb Wilson-Vandenberg; Sam McClatchie; J. Anthony Koslow; Brice X. Semmens (Frontiers in Marine Science, 2019)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Loggerhead Turtles (Caretta caretta) in the California Current: Abundance, Distribution, and Anomalous Warming of the North Pacific - Tomoharu Eguchi; Sam McClatchie; Cara Wilson; Scott R. Benson; Robin A. LeRoux; Jeffrey A. Seminoff (Frontiers in Marine Science, 2018)

Long Time Series in US Fisheries Oceanography - Sam McClatchie; Janet Duffy-Anderson; John Field; Ralf Goericke; Dave Griffith; David Hanisko; Jonathan Hare; Joanne Lyczkowski-Shultz; William Peterson; William Watson; Edward Weber; Glenn Zapfe (Oceanography, 2014)

A Wave Glider Approach to Fisheries Acoustics: Transforming How We Monitor the Nation's Commercial Fisheries in the 21st Century - Charles Greene; Erin Meyer-Gutbrod; Louise McGarry; Lawrence Hufnagle; Dezhang Chu; Sam McClatchie; Asa Packer; Jae-Byung Jung; Timothy Acker; Huck Dorn; Chris Pelkie (Oceanography, 2014)

Importance of scale to the relationship between abundance of sardine larvae, stability, and food - Sam McClatchie; Paul J. Rogers; Lachie McLeay (Limnology and Oceanography, 2007)
We used a spatially explicit regression model to relate sardine ( Sardinops sagax ) larval abundance to water column stability, phytoplankton, and zooplankton off South Australia. The distribution of sardine larvae was significantly associated with stability ( p p

Pelagic ecology of a northern boundary current system: effects of upwelling on the production and distribution of sardine ( Sardinops sagax ), anchovy ( Engraulis australis ) and southern bluefin tuna ( Thunnus maccoyii ) in the Great Australian Bight - TIM M. WARD; LACHLAN J. MCLEAY; WETJENS F. DIMMLICH; PAUL J. ROGERS; SAM MCCLATCHIE; ROGER MATTHEWS; JOCHEN KÄMPF; PAUL D. VAN RUTH (Fisheries Oceanography, 2006)
Shelf waters of southern Australia support the world's only northern boundary current ecosystem. Although there are some indications of intense nitrate enrichment in the eastern Great Australian Bight (GAB) arising from upwelling of the Flinders Current, the biological consequences of these processes are poorly understood. We show that productivity in the eastern GAB is low during winter, but that coastal upwelling at several locations during the austral summer–autumn results in localized increases in surface chlorophyll a concentrations and downstream enhancement of zooplankton biomass. Sardine ( Sardinops sagax ) and anchovy ( Engraulis australis ) eggs and larvae are abundant and widely distributed in shelf waters of the eastern and central GAB during summer–autumn, with high densities of sardine eggs and larvae occurring in areas with high zooplankton biomass. Egg densities and distributions support previous evidence suggesting that the spawning biomass of sardine in the waters off South Australia is an order of magnitude higher than elsewhere in southern Australia. Sardine comprised >50% of the identified prey species of juvenile southern bluefin tuna (SBT, Thunnus maccoyii ) collected during this study. Other studies have shown that the lipid content of sardine from the GAB is relatively high during summer and autumn. We suggest that juvenile SBT migrate into the eastern and central GAB during each summer–autumn to access the high densities of lipid‐rich sardines that are available in the region during the upwelling period. Levels of primary, secondary and fish production in the eastern GAB during summer–autumn are higher than those recorded in other parts of Australia, and within the lower portion of ranges observed during upwelling events in the productive eastern boundary current systems off California, Peru and southern Africa.